'Comment on Saumitou et al. (2017): Elucidation of the genetic architecture of self‐incompatibility in olive: evolutionary consequences and perspectives for orchard management'. (29th June 2017) - Breton, Catherine; Koubouris, Georgios; Villemur, Pierre; Bervillé, André Jean
Abstract: The new self‐incompatibility system (SI) was presented by Saumitou‐Laprade, Vernet, Vekemans et al. (2017). Evolutionary Applications based on 89 crosses between varieties in the olive tree. Four main points are not clear. We are examining here as follows: (i) the assertion that the self‐incompatibility system is sporophytic was not sustained by pollen germination data; (ii) surprisingly, the new model does not explain that about one‐third of pairwise combinations of olive varieties leads to asymmetric fruit setting; (iii) DNA preparation from one seed may contain two embryos, and thus, embryos should be separated before seed extraction; (iv) although effective self‐fertility in olive varieties was reported by many studies, the DSI model fails to explain self‐fertility in some olive varieties. Moreover, we cannot discuss result data, as science cannot be verified because variety names were encoded, this does not allow comparison of data with previous works. The DSI model on olive self‐incompatibility should explain more features than the model based on four dominance levels shared by six S‐alleles. Perspectives for orchard management based on this model may face serious limitations. An olive variety does not have a fifty percent chance of cross‐incompatibility, but surely fewer, and thus, the sporophytic system limits fruit production. Evolutionary perspectives of self‐incompatibility in Oleaceae should include data from the Jasmineae tribe that displays heterostyly SI.